(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An investigation was carried out in the Matshaya Rani (fish queen) Fish sanctuary to evaluate the hydrographic status, natural food and SIS (small indigenous species) abundance in the old Brahmaputra River near the BAU campus. There were three treatment sites- inside sanctuary, upstream and downstream of the sanctuary named as treatments T1, T2 and T3, respectively. A number of water quality parameters such as temperature (°C), transparency (cm), depth (cm), water velocity (m sec-1), pH,dissolved oxygen (mg l-1), conductivity (?s cm-1), TDS (mg l-1), alkalinity (mg l-1), phosphate-phosphorus (mg l-1), nitratenitrogen (mg l-1), ammonia-nitrogen (mg l-1) and chlorophyll-a (?g l-1) were recorded and were found within the suitable range for natural food and SIS in different treatments. Among all the water quality parameters, only water transparency and depth showed significant difference (P < 0.05) among the treatments. Forty three genera of phytoplankton belonging to Bacillariophyceae (10), Chlorophyceae (22), Cyanophyceae (8), and Euglenophyceae (3) and nine genera of zooplankton were identified belonging to Rotifera (4) and Crustacea (5) in all the treatments. None of plankton group except Cyanophyceae and Rotifera showed significant difference (p < 0.05) among the treatments. Thirty two species of SIS under ten groups were found in different treatments. The highest number of species was found in treatment T1 (30) followed by T2 (25) and T3 (24). The catfishes, loaches and minnows dominated among thirty two species caught from the sampling sites. The highest numbers of species were found in April and May and the least species were found the month of January. Significant inter month and inter site variation (P < 0.05) in numerical abundance of fish observed in the study area. Notable endangered fishes, Kanchan puti- (Puntius conchonius), Balichata Acanthocobitis botia), Indian torrent catfish-Amblyceps mangois and Chaka- (Chaca chaca) species were only found in Matshaya Rani Fish sanctuary. The natural food abundance and SIS diversity were significantly more in the inside of Matshaya Rani Fish sanctuary than both the upstream and downstream of the sanctuary. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11599 J. Environ. Sci. & Natural Resources, 5(1): 319-328, 2012